Analisis Strategi Pemasaran Syariah Produk Gadai Emas (Rahn) di Pegadaian Syariah: Studi Pada Pegadaian Unit Pelayanan Syariah Simpang Mayang Kota Jambi - Syahira Syahira; Usdeldi Usdeldi; Muhammad Taufik Ridho (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2024)
This research discusses the Analysis of Sharia Marketing Strategy for Gold Pawn Products (Rahn) at Sharia Pawnshops. Studies at the Pawnshop Sharia Service Unit Simpang Mayang Jambi. The aim of this research is to describe how marketing is carried out at Pegdaian Syariah Simpang Mayang, Jambi City, seen from the Sharia Marketing Indicators and what the obstacles are in marketing its products, especially Gadai Syariah (Rahn) products. This research is field research using descriptive qualitative methods. Data collection involves observation, interviews and documentation. Test the validity of this research using triangulation techniques. The subjects in this research were employees or marketers of Pegadaian Syariah Simpang Mayang, Jambi City and customers, with three employee informants and three customer informants. The results of this research indicate that marketers at the Simpang Mayang Syariah Pegadaian, Jambi City do not fully meet the characteristics of a sharia marketer. It can be seen from the Four Sharia Marketing Indicators that have not been fully implemented. There are 4 Marketing Indicators in Sharia Marketing. Of the 4 (Four) marketing indicators, only Ethical (akhlaqiyah) and Realistic (al-waqi'iyyah) have been fully implemented, while Theistic (rabbaniyah) and Humanistic (al-insaniyyah) have not been fully implemented. . There are obstacles for the Sharia Pawnshop Unit Simpang Mayang Jambi City in marketing its products, especially Sharia Pawnshop (Rahn) products. Such as trust from customers, the double duty of each employee and competition from other financial institutions.